PID Controller Implementation on Animal Experimental Treadmill for Heart Medicine Purpose - Melinda, Melinda; Ridwan, Muhammad; Nurbadriani, Cut Nanda; Yunidar, Yunidar (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
Experimental animals such as rats are often used for medical research and therapy, such as cardiologists who use a special treadmill to measure the heart health of rats by training walking or running in order to determine the appropriate dose for individuals before being applied to their patients. This research designed a system that is operated by the speed of a DC motor. To control the system, it is proposed to implement a Proportional Integral Derivative (PID) control that is able to stabilize the rotation of the DC motor based on the BPM value recorded by the encoder sensor. The value is used as feedback to the PID control, so that it can control the speed of the DC motor and work optimally and stably under load or no load. Adding a limit switch as a fatigue zone to determine the final duration. This system was tested on several objects, namely 4-month-old rats with a mass of 211 grams, 224 grams, 230 grams, and 240 grams and 2-month-old rats with a mass of 24 grams, 27 grams, 28 grams, and 30 grams. The results show that the speed reading using PID control is in accordance with the constants Kp = 17, Ki = 7, and Kd = 1. This test has a percentage overshoot (%) of 5% and an average rise time value of 0.14 seconds. System performance with a percentage accuracy of 90% starting from a setpoint of 35 m/min.